Techno‐economic analysis of cellulosic ethanol conversion to fuel and chemicals. (26th April 2022) - Phillips, Steven D.; Jones, Susanne B.; Meyer, Pimphan A.; Snowden‐Swan, Lesley J.
Abstract: In this paper, we describe multiple scenarios to assess the techno‐economic results of producing hydrocarbon fuels from corn stover‐derived ethanol and the impact of co‐producing higher‐value, ethanol‐derived n ‐butanol and 1, 3‐butadiene to improve economic feasibility. In our baseline process, the stover‐derived lignin is burned for its energy content to raise process steam and electricity. We evaluated an alternative approach based on the same stover‐to‐ethanol process, but instead of burning residual lignin to produce heat and electricity, it was fed to a hydrothermal liquefaction process and converted into hydrocarbon fuel, while the ethanol from fermentation is used to make only butanol or butadiene. Our results indicate that the hydrothermal liquefaction pathways have significant cost advantages over the pathways that burn the lignin. For comparison purposes, two more scenarios were evaluated based on the assumption that ethanol was purchased at market prices and converted to butanol or butadiene exclusively. This comparison evaluates the economics for making higher‐valued chemicals which, in the absence of incentives, would be the most profitable approaches in our study. The results for these evaluations indicated that the ethanol‐to‐butanol economics were generally favorable and achieved or exceeded the 10% internal rate of return target. The butadiene process had less favorable economic performance in some years when the market price for butadiene was less than the selling price needed to achieve the internal rate of return. Economic incentives for low‐carbon chemicals and fuels were not considered in our analysis. © 2022 Battelle Memorial Institute. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.